Avaliação auditiva em neonatos e lactentes utilizando emissões otoacústicas transientes, timpanometria e reflectância de potência - Ticianna Garambone de Cerqueira Lima Monteiro (2014)
Introduction: The audio trial in newborns allows us to detect hearing problems early in life. However, middle ear diseases can make the diagnosis more difficult. Aim: To evaluate the power reflectance measurement based on the wide band reflectance as an indicator of the middle ear disease and to compare it to the tympanometry. Method: Case study, this study evaluated 105 newborns and infants who participated in the audio trial at the Clinics Hospital from the Federal University of Minas Gerais in 2013. The following exams were performed: transient otoacoustic emissions, power reflectance and tympanometry. Results: about 95% past the otoacoustic emissions evaluation;the specificity of power reflectance in all frequencies researched ranged from 75.3% to 95.9%, and the specificity of tympanometry in 1.000 Hz ranged from 83% to 87.2%, and there was a concordance amongst the exams. Conclusion: The outcome of the power reflectance exam in 2.000Hz and 3.000Hz showed a correlation with the results of tympanometry and otoacoustic emissions, and those were the most adequate frequencies to determine the middle ear disease through power reflectance measurement. It was also observed that the values of power reflectance above standards suggested the presence of liquid in the middle ear, thus a conductive hearing loss.